A Curcumin-Loaded Liposomal Thermoresponsive In Situ Nasal Gel for Brain Targeted Antidepressant Therapy - Ling Li; Yan Sun; Guanlong Li; Zhi Li; Haocheng Wang; Zhuoyan Li; Hongxing Wang; Yanpeng Jia (ACS Applied Materials & Interfaces, 2026)
Abstract Major depressive disorder (MDD) is a chronic and recurrent neuropsychiatric condition that imposes a profound burden on individuals and society. Despite its increasing prevalence, effective therapeutic options that provide rapid, sustained, and well-tolerated relief remain limited. Mounting evidence implicates neuroinflammation, particularly microglial activation, as a critical pathological driver of MDD. Reprogramming reactive microglia toward a neuroprotective phenotype has thus emerged as a promising strategy to ameliorate MDD-related symptoms. Herein, we developed a thermoresponsive in situ gelling intranasal delivery system (TAT-lipo@Cur Gel), which combines TAT-modified liposomes with a Pluronic F127/F68 hydrogel matrix to enhance nose-to-brain transport and prolong mucosal retention of curcumin. Biodistribution studies demonstrated that intranasal administration of TAT-lipo@Cur Gel markedly enhanced curcumin accumulation in the brain. In a chronic unpredictable mild stress (CUMS) mouse model, TAT-lipo@Cur Gel significantly alleviated depressive-like behaviors and restored behavioral performance. Mechanistically, this effect was mediated through suppression of neuroinflammation, as evidenced by reduced expression of pro-inflammatory cytokines, enhanced microglial polarization toward the M2 phenotype, and alleviated astrocytic dysfunction. In summary, our findings establish TAT-lipo@Cur Gel as a safe, non-invasive, and effective intranasal delivery platform for the treatment of MDD. With its excellent biocompatibility, reduced dosing frequency, and shortened treatment duration, this strategy holds great promise for clinical translation in managing MDD and potentially other neuroinflammatory CNS disorders.